2012
DOI: 10.1590/s0100-204x2012000800011
|View full text |Cite
|
Sign up to set email alerts
|

Seleção precoce para produção de grãos em café arábica pela avaliação de caracteres morfológicos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a viabilidade da seleção precoce em café arábica, por meio do emprego de correlações entre caracteres morfológicos e de produção de grãos. Foram avaliados 269 acessos de Coffea arabica, entre cultivares, híbridos e genótipos selvagens, oriundos do banco de germoplasma de café da Epamig, em Patrocínio, MG. Utilizou-se o delineamento em blocos ao acaso, com duas repetições, no espaçamento 3,5x0,8 m, com parcelas de dez plantas. Os caracteres morfológicos foram avalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
1
9
0
2
Order By: Relevance
“…The plagiotropic branch length was positively moderate-correlated with the number of nodes in plagiotropic branches, distance between nodes in plagiotropic branch, orthotropic branch length, canopy diameter, and plant height. Teixeira et al (2012) found a high correlation between plagiotropic branch length and number of nodes and plant height, and also that the plagiotropic branch length had a significant direct effect on crop production. Another study also indicated a moderate correlation between length and number of nodes in plagiotropic branches, and a high correlation value between plagiotropic branch length and plant height (Carvalho et al, 2010).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The plagiotropic branch length was positively moderate-correlated with the number of nodes in plagiotropic branches, distance between nodes in plagiotropic branch, orthotropic branch length, canopy diameter, and plant height. Teixeira et al (2012) found a high correlation between plagiotropic branch length and number of nodes and plant height, and also that the plagiotropic branch length had a significant direct effect on crop production. Another study also indicated a moderate correlation between length and number of nodes in plagiotropic branches, and a high correlation value between plagiotropic branch length and plant height (Carvalho et al, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…In order to identify the variables that contributed to the multi-collinearity emergence, eigenvalues and eigenvectors analyses were performed. The multi-collinearity is classified according to the condition number (CN) values as follows: weak (CN < 100), moderate (100 < CN < 1,000) or strong (CN > 1,000) (Teixeira et al, 2012). The CN value in this study was above acceptable, thus some variables were removed by means of principal components, eliminating the component with highest weight from the high vector of the smallest vector.…”
Section: Leaf and Branch Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freitas (2004) observou correlações genotípicas entre o diâmetro de caule e os caracteres altura da planta, número de ramos plagiotrópicos, comprimento dos ramos plagiotrópicos e número de internódios em dezenove cultivares de café (Continua) arábica. De acordo com Teixeira et al (2012) existe correlação positiva entre produtividade do cafeeiro com o comprimento do primeiro ramo plagiotrópico e o número de nós no ramo; ademais, as cultivares que possuem essas características tendem a ser mais produtivas.…”
Section: Npf ---N° ---unclassified
“…Dessa forma, é possível realizar uma seleção para cultivares mais produtivas através de uma pré-seleção no período juvenil, observando características que se correlacionam com a produtividade (Freitas et al, 2007). Teixeira et al (2013) afirmam que o comprimento do 1º ramo plagiotrópico, vigor, diâmetro do caule e número de nós do 1º ramo plagiotrópico são características de grande importância para diferir os genótipos de café arábica em estádio juvenil.…”
Section: Npf ---N° ---unclassified